A diversidade é a regra: discursos pseudonaturalistas e sua influência na formação das identidades e construção do direito - Luiz Carlos Garcia (2021)
When the subject is scientific knowledge, if a name were chosen to synthesize the moment experienced by society, the era of opposites would fit very well. In the same way that science and everything that has been discovered and tested is questioned, the so-called scientific knowledge is used as a source of affirmation to justify social, cultural and political choices. If in the past religion served as a source of explanation for all the natural and social phenomena that occurred, today this place has been assumed by science. An idea of scientific purism was created that gives, to what is said, the condition of true dogma, something that cannot and should not be questioned. This context is the basis for naturalization processes to take place, in order to give the status of natural or normal to situations and facts that are imminently social. And so prevent questionings and discussions from happening. The consequence of these naturalizing processes is the possibility of discourses headed by groups that are in a position of power in society to be presented as scientific truths, as essential conditions of humanity and thus promote the denial of the other, a true escalation on identities and subjectivities in less or more human. Being especially relevant when it comes to gender or sexual identities. All these processes justify how certain social groups will be treated and often legitimize violence and segregation on the part of the population, the State, social institutions and the Law. Therefore, what this thesis proposes is the discussion of how naturalization processes take place and are used as power/control in today's society, shaping bodies and identities and thus legitimizing the maintenance of a way of living in a society that has standardization and exclusion as a framework for its entire structure.